2017
DOI: 10.1007/s10620-017-4572-4
|View full text |Cite
|
Sign up to set email alerts
|

Medical Therapies for Stricturing Crohn’s Disease: Efficacy and Cross-Sectional Imaging Predictors of Therapeutic Failure

Abstract: Anti-TNF combotherapy seemed to prevent therapeutic failure, and cross-sectional imaging should be systematically performed to help medical management in stricturing Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 33 publications
4
40
0
Order By: Relevance
“…Despite the best therapy, up to 66% of patients with stricturing CD fail medical therapy and 40% fail endoscopic dilation and thus will require surgery. Preserving bowel length is essential to the treatment of these patients.…”
Section: Management Of Crohn's Disease Associated Stricturesmentioning
confidence: 99%
“…Despite the best therapy, up to 66% of patients with stricturing CD fail medical therapy and 40% fail endoscopic dilation and thus will require surgery. Preserving bowel length is essential to the treatment of these patients.…”
Section: Management Of Crohn's Disease Associated Stricturesmentioning
confidence: 99%
“…In the meanwhile, previous reports also indicated that the presence of intestinal complications was known to be one of lower efficacy of anti-TNF agents 56. The aim of our study was, therefore, to verify the effect of removal of intestinal complication by surgery on recovery of the efficacy of biologics.…”
mentioning
confidence: 86%
“…13 In multivariate analysis, small stricture luminal diameter and increased stricture wall thickness were predictors of strictures for which medical therapy typically fails. 14 The patients should be educated about their disease and the operative options because they commonly possess only rudimentary insight. Many surgeons feel that biologic agents should be discontinued several weeks prior to an elective procedure because they might interfere with the normal immune response and increase the likelihood of postoperative complications, although the impact of these agents is controversial and no strictureplasty-specific evidence is currently available.…”
Section: Preoperative Evaluation and Optimizationmentioning
confidence: 99%